2005
DOI: 10.1111/j.1365-2559.2005.02132.x
|View full text |Cite
|
Sign up to set email alerts
|

COX‐2 expression in DCIS: correlation with VEGF, HER‐2/neu, prognostic molecular markers and clinicopathological features

Abstract: Our results suggest that COX-2 is highly expressed in DCIS and takes part in the molecular pathway implicated in progression of breast cancer and may provide a rationale for targeting COX-2 in preinvasive breast cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
48
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 33 publications
10
48
1
2
Order By: Relevance
“…COX-2 has been shown to be expressed in both ductal carcinoma in situ and invasive ductal carcinoma, but not in normal breast tissue in several research articles [16][17][18]. We also saw COX-2 expression in invasive ductal carcinoma, lobular carcinoma and ductal carcinoma in situ but not in fibroadenoma and benign breast disease (Figs.…”
Section: Discussionsupporting
confidence: 54%
“…COX-2 has been shown to be expressed in both ductal carcinoma in situ and invasive ductal carcinoma, but not in normal breast tissue in several research articles [16][17][18]. We also saw COX-2 expression in invasive ductal carcinoma, lobular carcinoma and ductal carcinoma in situ but not in fibroadenoma and benign breast disease (Figs.…”
Section: Discussionsupporting
confidence: 54%
“…The study revealed the presence of COX-2 protein in 13 of 13 invasive human breast tumors, but not in samples of normal breast tissue. There was a statistically significant linear association between COX-2 and high (> 50%) tumor cell density (P < 0.01) with COX-2 protein localized to tumor cells.Subsequently, molecular biologists from multiple independent laboratories have consistently observed COX-2 over-expression in all stages of breast cancer [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] . Figure 1 shows the mean frequency of specimens over-expressing COX-2 in the progression of mammary carcinogenesis.…”
mentioning
confidence: 99%
“…Significantly elevated frequencies of specimens with high COX-2 expression were also observed in premalignant lesions such as atypical hyperplasia (44%) and ductal carcinoma in situ (65%). Furthermore, several of the studies suggest that COX-2 expression is correlated with the metastatic spread of breast cancer and has strong potential as a prognostic indicator of disease severity and progression [30,31,35,[37][38][39] . By comparison, all studies have found negligible or very weak focal COX-2 expression in normal tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 Although VEGF-C production and lymphangiogenesis was a direct consequence of COX-2 expression in human breast cancer, 17 we found that HER-2, often co-expressed with COX-2 in human breast cancer, had no direct role in VEGF-C upregulation or lymphangiogenesis, and that its role, if any, was COX-2 dependent. 21 The facts that COX-2 is overexpressed in about half of breast cancer specimens 7 inclusive of DCIS 24 and invasive carcinomas, 21 and has multiple roles in breast cancer progression and metastasis, make this molecule a reasonable therapeutic target. Recent safety concerns related to the cardiovascular side effects of high dose COX-2 inhibitors 25,26 have led to the search for alternative targets downstream of COX-2, which would spare the vaso-protective prostacyclins.…”
mentioning
confidence: 99%